(untitled) (Comprehensive Journal of Science, 2025)
Drawing is considered one of the fundamental artistic activities used to develop students’ skills at different educational stages. Its role is not limited to being a means of entertainment or self-expression, but it also extends to enhancing cognitive, motor, and creative abilities. Drawing is regarded as a key educational activity that contributes to the overall development of students’ capacities in various forms. This study aims to highlight the role of drawing and its ability to develop students’ skills and competencies. Drawing plays a significant role in improving writing, reading, critical thinking, and problem-solving skills. The research builds on a review of previous studies that addressed this topic, focusing particularly on the development of students’ visual culture. A study sample was selected to evaluate the impact of practicing drawing on students in basic education. Questionnaires were distributed to teachers of different subjects in the basic education stage, and the collected data were analyzed using a descriptive-analytical approach. The bindings indicate that most respondents agreed that drawing helps students understand and assimilate information more easily and quickly. More over, students showed the ability to illustrate lessons and replicate text book drawings in a highly creative manner, reflecting their artistic and imaginative skills.